(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the attitudes of customers toward Social Media Marketing of fast-moving consumer goods (FMCGs) in Kozhikode. In recent years, social media platforms have become a critical marketing tool for businesses aiming to engage with consumers and promote their products. This research aims to understand how customers perceive social media marketing efforts by FMCG companies and the factors influencing their attitudes. Data was collected through a structured questionnaire distributed to a diverse sample of customers in Kozhikode. The survey included questions on the frequency of social media usage, the impact of social media advertisements on purchasing decisions, and the overall sentiment toward social media marketing practices. The findings indicate that while a significant portion of the customer base is actively engaged on social media, their attitudes towards marketing efforts vary based on demographic factors, such as age, gender, and education level. The study reveals that younger consumers tend to have a more favorable view of social media marketing, appreciating its convenience and personalized content. In contrast, older consumers are more skeptical and less influenced by social media promotions. This research provides valuable insights for FMCG companies aiming to optimize their social media marketing strategies. By understanding customer attitudes, businesses can tailor their approaches to enhance engagement and drive sales in the dynamic market of Kozhikode.